2020
DOI: 10.3390/ejihpe10010029
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Heart Rate Variability Using Commercially Available Devices in Healthy Children: A Validity and Reliability Study

Abstract: Heart rate variability (HRV) is an accepted method for determining autonomic nervous system activity and cardiovascular risk in various populations. This study assessed the validity and reliability of a commercially available finger photoplethysmography (PPG) system for measuring pediatric HRV in a real-world setting. Sixteen healthy children (4.06 ± 0.58 years) were recruited. The PPG system was compared to the Polar H10 heart rate (HR) sensor validated against ECG (gold standard) for HRV measurement. Seated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 47 publications
0
37
0
2
Order By: Relevance
“…We did not assess the efficacy of the Polar H10 strap at collecting data, rather the phone applications at their ability to process the data. The Polar H10 has already been validated by previous researchers (Gilgen-Ammann et al, 2019 ; Speer et al, 2020 ) and has been used by researchers as a standard criterion device for quantifying cardiovascular metrics (Müller et al, 2019 ; Weaver et al, 2019 ). The observed bias for CAMHRV was higher than previous research conducted on CAMHRV which reported 6 ms bias when compared to an FDA-approved pulse oximeter (Pai et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess the efficacy of the Polar H10 strap at collecting data, rather the phone applications at their ability to process the data. The Polar H10 has already been validated by previous researchers (Gilgen-Ammann et al, 2019 ; Speer et al, 2020 ) and has been used by researchers as a standard criterion device for quantifying cardiovascular metrics (Müller et al, 2019 ; Weaver et al, 2019 ). The observed bias for CAMHRV was higher than previous research conducted on CAMHRV which reported 6 ms bias when compared to an FDA-approved pulse oximeter (Pai et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The electrodes of the Polar H10 were moistened with room temperature water prior to being placed on the xiphoid process of the sternum, with the chest strap fitted around the participant’s chest (just below the chest muscles) [ 54 ]. The electrocardiography (ECG)-unit of the Polar H10 records electric signals of the heart with a frequency of 1000 Hz and has been previously validated against the 3-lead ECG, which is the gold standard in this field [ 55 ]. Thus, the Polar H10 fulfills the technical requirements to quantify HRV, as defined by several methodological guidelines (e.g., measurement frequency > 200 Hz) [ 56 , 57 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…During exercise, the VR Health Exercise Tracker app automatically recorded exercise data via Bluetooth from the Polar monitor. The Polar electrocardiographic chest strap monitors, including the H10, have over two decades of published studies demonstrating strong psychometric properties to support their use for measuring heart rate among both youth and adults [ 31 - 33 ]. VR Health Exercise Tracker records and displays in real time the following data: exercise intensity (heart rate), calories, and exercise duration (minutes).…”
Section: Methodsmentioning
confidence: 99%